Investigation of Road Bank Failures based on Mineralogical Composition Studies in Kano-Abuja Road Northern, Nigeria - Mohd Khairul Amri, Kamarudin; Roslan, Umar (2018)
This article investigated the general compositions of the areas (the road) including the geology, mineralogy, and geochemistry to explore the reason for the road failure. The zone is underlain basement (storm cellar) and sedimentary rocks of different textures, mineralogy, and geochemistry. The results implies that the areas that is most stable along the road portions is underlain by the granite-gneiss, granites, amphibole schist and quartz, schist and small sandstone while portions with the failures are underlain by mica schist, phyllite, and coarse-grained granite. It is apparently sure from this study that poor quality metasedimentary rocks constitute the formation of the failed portions. However, the high numbers of the sediment and sandstone present in the area that can easily be weathered due to the climate variation have increased the failure. In conclusion, the result will help the engineers during reconstruction of these parts need to be excavating deeply and replace with granite-gneiss, granites, amphibole schist and quartz for better result.